Kitchen equipment adoption in school canteen: technology acceptance model approach / Nadia Liana Mohd Karim, Norfezah Md Nor and Arnieyantie Abd Hadi - Mohd Karim, Nadia Liana; Md Nor, Norfezah; Abd Hadi, Arnieyantie (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
One of the most recognised contributing factors to food poisoning incidents is improper food handling in terms of storage and temperature. To prevent such food safety violations, food manufacturing businesses, specifically kitchen plants, must utilise appropriate cooking equipment. The school canteen was chosen as the research's focus group to assess the levels of technology usage in day-to-day operations. The questionnaire, which was circulated through internet channels, was completed by 76 school canteen food handlers. The study's findings revealed a positive relationship between perceived usefulness of adoption, perceived ease of use of adoption, and foodservice operator willingness to invest in kitchen equipment technology in school canteens with the intention to use the kitchen equipment.